A diversidade de práticas produtivas de famílias agroextrativistas na Amazônia - FELIZARDO, Alciene Oliveira (Universidade Federal do Pará, 2021)
The present work aims to characterize the productive practices of Amazonian agroextractive families, evidencing the process of insertion of bird breeding provided by participation in a local project. For that, eleven families from the Capim, Caripetuba and Xingu Islands, Abaetetuba municipality in Pará, were interviewed. The study identified that the agroextractive families from the Capim, Caripetuba and Xingu Islands are heterogeneous with regard to the availability of resource bases (social and materials), composition, organization and functioning of the family-establishment system. Agroextractive families were classified into three types a) type I: restricted base of material resources with predominance of external income; type II: material resource base with medium diversity and income centered on the extraction of açaí, fish and shrimp; and, type III: material resource base with high diversity and multiple sources of income. This reveals that the agroextractive families that benefit from the local project develop different practices guided by the particularities of the familyestablishment system that imply permanence or resistance in the face of standardized agricultural development projects.